"عقد السمسرة بين الواقع والشرع سوق البطاطا بوادي سوف أنموذجا -دراسة وصفية- " - بن مبارك, عبد الحليم (University of Eloued جامعة الوادي, 2020)
"لقد حررنا بحثنا هذا بعنوان ""عقد السمسرة بين الواقع والشرع، سوق البطاطا بسوف أنموذجا"" دراسة ميدانية، بغرض الإجابة عن التساؤل حول ماهية عقد السمسرة، وهل الضرب الواقع بأسواق سوف من التوسط أهو من السمسرة؟ أم هو صنف آخر من العقود؟ فقدمناه في ثلاثة مباحث، الأوَّلان منهما حول الجانب النظري من البحث، والأخير حول الجانب الواقعي، فقدمنا الأول في مطلبين، عرفنا في الأول بمصطلحات البحث، وبينا في الثاني مشروعيته، والمبحث الثاني فصلناه في مطلبين، الأول منهما نسجناه في بيان تكييف هذا العقد، أما الثاني ففي أركان وشروط هذا العقد، أما المبحث الثالث والأخير فعرفنا فيه بالمنطقة في المطلب الأول، أما الثاني فكان في واقع سوق البطاطا بسوف، ودور السماسرة فيه. فكانت زبدة بحثنا، أن السمسرة عقد مستقل بذاته، لا يتقيد يعقد آخر لا ينفك عنه، ولعل أهم ما نوصي به، هو توجيه الرسائل العلمية للواقع المعيش في بلدنا."Summary : We have edited this research entitled “Brokerage Contract Between Reality and Sharia, Potato Market in El- Oued as a sample ”, a field study, aims to answer the questions : What a brokerage contract is ? Is the kind of mediation that widespread in El-oued markets considered as a from brokerage? Or is it another type of contracts? This thesis is consisted of three chapters ; the first and the second chapters deals with the theoretical side whereas the third one concerns with the practical side. The first chapter consists of two parts ; the first one defines the terms of the thesis and the second one clarifies its legitimacy and rightness. The second chapter consists of two topics ; the first one indicates the adaptation of this contract ,while the second one concerns with the contract founds and its conditions. In the last chapter, we have introduced 'Oued Souf 'region in the first part and we have indicated the Potatoes market reality and the role of brokers on this market. The final results we have found that the brokerage is an independent contract that does not restrict with another contract. finally , we recommend that dissertations should be sent to our society.
مذكرة ماستر تخصص فقه مقارن واصوله
Keywords: "عقد - السمسرة - الواقع - الشرع،; Contract - brokerage - reality - Sharia